Enhancing the Productivity of Maize-Based Systems in Drought-Prone Areas of Malawi through Maize-Sweetpotato Intercropping - Longwe, K.; Munda, E.; Chipungu, Felistus P.; Mello Kapezi, R.; Kuweruza, F.; Jogo, W. (2024)
Maize is central to food security in Malawi, but its productivity is increasingly threatened by unpredictable rainfall, frequent droughts linked to climate change and high costs of inorganic fertilisers. Crop diversification through intercropping offers a promising strategy to enhance maize-based systems productivity and resilience to climate change. This study examined the productivity and resource use efficiency of maize-sweetpotato intercropping system in drought-prone areas in Malawi. The experiment evaluated strip intercropping arrangements against sole maize and sweetpotato at two sites in Utale and Masaula Extension Planning Areas (EPAs) in Balaka and Zomba Districts respectively during the 2023/2024 agricultural season which was characterized by low rainfall due to El Nino. The results showed maize grain yield was significantly higher in sole maize (SM, 1.5 t/ha) than any of the intercropping arrangements (p < 0.02) while no significant differences (p = 0.9) were observed in harvest index across treatments. Sweetpotato yield was significantly affected by intercropping arrangements (p < 0.001), highest obtained in sole sweetpotato (SP, 14.2 t/ha) but did not differ with intercrops comprising of two ridges of maize at 50cm alternating with two ridges of sweetpotato at 100cm (T2, 13.1 t/ha), four ridges of maize at 50cm alternating with four ridges of sweetpotato at 100cm (T6, 13.1 t/ha), and four ridges of maize at 75cm alternating with four ridges of sweetpotato at 100cm (T8, 11.4 t/ha). Intercrops with two ridges of maize at 50cm alternating two ridges of sweetpotato at 75cm (T1), two ridges of maize at 50cm alternating with two ridges of sweetpotato at 100cm (T2), and four ridges of maize at 75cm alternating four ridges of sweetpotato at 100cm (T8) had land equivalent coefficient (LEC) > 0.25 and Land equivalent ratio (LER) > 1 at both sites indicating more efficient land use compared to monocropping. Sweetpotato contributed a greater proportion to the LER, and the positive correlation (R²) between sweetpotato yield and sweetpotato equivalent yield (PEY) suggests its potential to enhance the economic efficiency of maize-based systems. Maize-sweetpotato intercrops with two ridges of maize at 50cm alternating with two ridges of sweetpotato at 75cm (T1), two ridges of maize at 50cm alternating with two ridges of sweetpotato at 100 cm (T2), and four ridges of maize at 75cm alternating with four ridges of sweetpotato at 100cm (T8) are recommended for enhancing productivity and economic returns in drought-prone areas. Further research is needed to optimize plant density and spatial arrangement to maximize yields without sacrificing resource efficiency.